The New Science - Vico, Giambattista; Taylor, Jason; Miner, Robert C. (New Haven : Yale University Press, 2020)
A fresh translation of The New Science, with detailed footnotes that will help both the scholar and the new reader navigate Vico's masterpiece The New Science is the major work of Italian philosopher Giambattista Vico. First published in 1725 and revised in 1730 and 1744, it calls for a reinterpretation of human civilization by tracing the stages of historical development shared by all societies. Almost unknown during his lifetime, the work had a profound influence on later thinkers, from Montesquieu and Marx to Joyce and Gadamer. This edition offers a fresh translation and detailed annotations which enable the reader to track Vico's multiple allusions to other texts. The introduction situates the work firmly within a contemporary context and newly establishes Vico as a thinker of modernity.
An Explication of the Picture Put Forward as the Frontispiece, to Serve as the Introduction to the Work -- Book One. On the Establishment of Principles -- Book Two. On Poetic Wisdom -- Book Three. On the Discovery of the True Homer -- Book Four. On the Course That the Nations Make -- Book Five. On the Recurrence of Human Things During the Resurgence That the Nations Make -- Conclusion of the Work--Concerning an Eternal Natural Republic, Best in Each of the Kinds of Republic Ordered by Divine Providence
Online resource; title from digital title page (viewed on January 03, 2020).
JSTOR
Keywords: Philosophy -- Early works to 1800.; Social sciences -- Early works to 1800.; Poetry -- Early works to 1800.; Philosophie -- Ouvrages avant 1800.; Sciences sociales -- Ouvrages avant 1800.; Poésie -- Ouvrages avant 1800.; PHILOSOPHY -- Political; Philosophy; Poetry; Social sciences; Early works